Identification of Clonorchis sinensis in bronchoalveolar lavage fluid and peripheral blood using next-generation sequencing in a patient with septic shock: a case report and literature review - Weipeng Liu; Mengting Su; Dongjing Zhang; Siqi Liu; Yin Zhang; Zhengfei Yang (Emerging Microbes and Infections)
We present a case report of a 59-year-old male diagnosed with pancreatic cancer with multiple abdominal metastases, in whom metagenomic next-generation sequencing unexpectedly identified Clonorchis sinensis genomic sequences in both bronchoalveolar lavage fluid and peripheral blood specimens. Subsequent examination further confirmed the presence of viable C. sinensis eggs in the stool samples. The findings underscore the prognostic significance of enhanced diagnostic protocols for parasitic infections in oncological cases. This investigation demonstrates the clinical utility of molecular diagnostic approaches and alternative biological specimens for detecting C. sinensis infection.